Vol. 2 (2014, 2014)
The collection of materials of the V international research and practice conference "Science and Education" is the research and practice edition. It gives an opportunity for scientists and experts to get acquainted with achievements of the priority directions of modern science, to show the results of the researches, to exchange experience, to publish scientific articles that will promote productive scientific work, realization of creative potential, origin of new ideas and establishment of friendly relations and possibilities for cooperation.It includes the scientific articles of students, postdoctoral students, graduate students, research scientists of higher education institutions.